Olympic tourism - Weed, Mike (Amsterdam : Elsevier Science, 2008)
"Olympic Tourism is the first text to focus on the nature of Olympic tourism and the potential for the Olympic Games to generate tourism in the run up to and long after the hosting of a Games. Since the Sydney Games in 2000, successive Olympic hosts have shown an increasing interest in the issues surrounding the organisation, management and analysis of mega-event sport tourism. This text addresses these issues and using detailed case analysis of previous and future games, discusses how to maximise the success of managing tourism at these events."--Jacket
Sport, tourism and the Olympic Games -- Who are Olympic tourists? -- The detail of Olympic tourism -- Leveraging Olympic tourism -- Planning for Olympic tourism -- The winter Olympic games -- The games of the XXVII Olympiad in Sydney (2000) -- The games of the XXVIII Olympiad in Athens (2004) -- The games of the XXIX Olympiad in Beijing (2008) -- The games of the XXX Olympiad in London (2012).
Includes bibliographical references and index.
Keywords: OLYMPICS -- ECONOMIC ASPECTS